(untitled) (Prostor, 2024)
Architect Aleksander Saša Laslo (Celje, 1950 – Zagreb, 2014) was one of the leading historians of Croatian twentieth-century architecture, with a research scope centered on the city of Zagreb. Its aim was to investigate the processes of modernisation, tracing the evolution from high historicism and eclecticism through Art Nouveau to proto-functionalism and New Building (Ger. Neues Bauen, Cro. novo građenje) – viewed through building spatial-organisation, construction, and then inevitably form. Laslo’s interest, of course, extended beyond the mere physical structure of the building to wider social, economic, and cultural context, and dynamic knowledge exchange with Central Europe during that time, within which Laslo positioned the architecture of Zagreb. Methodologically, since the very beginning in the early 1980s, Laslo relied on exhaustive research, cataloguing, and contemporary research of Central European architecture. To mark the tenth anniversary of the death of this prominent researcher of Zagreb’s architectural heritage, this paper provides the first review of Laslo’s work, highlighting its comprehensiveness, integrity, and scientific method.